2020
DOI: 10.1002/anie.201913700
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Engineered Macrophage‐Derived Exosomes with Inflammation Tropism and Intrinsic Heme Biosynthesis for Atherosclerosis Treatment

Abstract: Atherosclerosis (AS) is a major contributor to cardiovascular diseases worldwide, and alleviating inflammation is a promising strategy for AS treatment. Here, we report molecularly engineered M2 macrophage‐derived exosomes (M2 Exo) with inflammation‐tropism and anti‐inflammatory capabilities for AS imaging and therapy. M2 Exo are derived from M2 macrophages and further electroporated with FDA‐approved hexyl 5‐aminolevulinate hydrochloride (HAL). After systematic administration, the engineered M2 Exo exhibit ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
143
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(143 citation statements)
references
References 59 publications
0
143
0
Order By: Relevance
“…Certainly, exosomal cargoes are not limited by miRNAs only but also by a lot of other candidate molecules such as proteins, lipids, enzymes, signaling molecules, which can exert their functional activities far from the exosome-producing cells. 84 Table 3 demonstrates that CDE cargoes could contain basically any purpose-built loaded nano-molecules for its ultimately release from the parental cells. It is evident that horizontal or paracrine transfer of these molecules, when received by the specific recipient cells in the TME or any distant metastatic niches, could facilitate the progression, invasion, and metastatic spread of cancer cells.…”
Section: Other Molecules (Proteins Enzymes Receptors Ligands or Smentioning
confidence: 99%
“…Certainly, exosomal cargoes are not limited by miRNAs only but also by a lot of other candidate molecules such as proteins, lipids, enzymes, signaling molecules, which can exert their functional activities far from the exosome-producing cells. 84 Table 3 demonstrates that CDE cargoes could contain basically any purpose-built loaded nano-molecules for its ultimately release from the parental cells. It is evident that horizontal or paracrine transfer of these molecules, when received by the specific recipient cells in the TME or any distant metastatic niches, could facilitate the progression, invasion, and metastatic spread of cancer cells.…”
Section: Other Molecules (Proteins Enzymes Receptors Ligands or Smentioning
confidence: 99%
“…Another in vitro study observed that when macrophages and SMC were treated with EC-derived EVs loaded with anti-miR-33a-5p, ATP-binding cassette transporter ABCA1 protein expression was increased and elevated apoAI-mediated cholesterol efflux was observed too [ 222 ]. Molecularly engineered EVs for treatment of atherosclerosis have also been investigated [ 223 ]. Wu et al, exploited M2 macrophage-derived EVs which were electoporated and loaded with the FDA approved compound, hexyl 5-aminolevulinate hydrochloride (HAL) [ 223 ].…”
Section: Evs As Therapeutic Delivery Vectorsmentioning
confidence: 99%
“…Molecularly engineered EVs for treatment of atherosclerosis have also been investigated [ 223 ]. Wu et al, exploited M2 macrophage-derived EVs which were electoporated and loaded with the FDA approved compound, hexyl 5-aminolevulinate hydrochloride (HAL) [ 223 ]. Administration of engineered EVs to apoE −/− mice under high fat diet showed reduced lesion area compared to control mice or mice receiving HAL or M2-derived EVs.…”
Section: Evs As Therapeutic Delivery Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes have emerged as an alternative to those exogenous nanoparticles [15,16]. These membraneenclosed vesicles with sizes of 40-150 nm are naturally secreted by various cell types, which endow them with fascinating natural properties such as low cytotoxicity, non-immunogenicity, desirable biocompatibility, speci c targeting capacity and prolonged systemic circulating ability [15,[17][18][19]. These superior properties making them ideal drug delivery nanocarriers.…”
Section: Introductionmentioning
confidence: 99%